Repetitive DNAs and Karyotype Evolution in Phyllostomid Bats (Chiroptera: Phyllostomidae) - Deon, Geize Aparecida; Ezaz, Tariq; Stornioli, José Henrique Forte [UNESP]; dos Santos, Rodrigo Zeni [UNESP]; Gomes, Anderson José Baia; Setti, Príncia Grejo; de Oliveira, Edivaldo Herculano Correa; Porto-Foresti, Fábio [UNESP]; Utsunomia, Ricardo [UNESP]; Liehr, Thomas; de Bello Cioffi, Marcelo (MDPI, 2025)
Bats are great models for studying repetitive DNAs due to their compact genomes and extensive chromosomal rearrangements. Here, we investigated the repetitive DNA content of two phyllostomid bat species, Artibeus lituratus (2nn = 30♀/31♂) and Carollia perspicillata (2n = 20♀/21♂), both harboring a multiple XY1Y2 sex chromosome system. Satellite DNA (satDNA) libraries were isolated and characterized, revealing four and ten satDNA families in A. lituratus and C. perspicillata, respectively. These sequences, along with selected microsatellites, were in situ mapped onto chromosomes in both species and phylogenetically related taxa. SatDNAs showed strong accumulation in centromeric and subtelomeric regions, especially pericentromeric areas. Cross-species mapping with C. perspicillata-derived probes indicated terminal localization patterns in other bat species, suggesting conserved distribution. Microsatellites co-localized with 45S rDNA clusters on the neo-sex chromosomes. Additionally, genomic hybridization revealed a male-specific signal on the Y1 chromosome, pointing to potential sex-linked repetitive regions. These findings confirm that bat genomes display relatively low amounts of repetitive DNA compared to other mammals and underscore the role of these elements in genome organization and sex chromosome evolution in phyllostomid bats.